Money & credit in Indian history : from early medieval times - Indian History Congress; Bagchi, Amiya Kumar (New Delhi : Tulika, 2002)
Papers presented at the 61st Session of Indian History Congress, January 2-4, 2001 at Calcutta.
Includes bibliography and index.
Keywords: Money -- India -- History -- Congresses; Credit -- India -- History -- Congresses; Banks and banking -- India -- History -- Congresses